When you see me : a novel - Gardner, Lisa (Gardner, Lisa. Detective D.D. Warren novel., 2020)
"#1 New York Times bestselling author Lisa Gardner unites three of her most beloved characters--Detective D. D. Warren, Flora Dane, and Kimberly Quincy--in a twisty new thriller, as they investigate a mysterious murder from the past . . . that points to a dangerous and chilling present-day crime"--